Making It Count : Statistics and Statecraft in the Early People's Republic of China - Ghosh, Arunabh, 1980- (Book collections on Project MUSE., 2020)
"Among the biggest challenges facing leaders of the newly established People's Republic of China (PRC) was how much they did not know. In 1949, at the end of a long sequence of wars, the government of one of the largest states in the world committed to fundamentally re-engineering its society and economy via socialist planning while having almost no hard, reliable statistical data about their own country. This book is a history of attempts made to resolve this "crisis in counting." Drawing on a wealth of official, institutional, and private sources culled from China, India, and the United States, the author explores the choices made and the effects they engendered through a series of vivid encounters with political leaders, professional statisticians, academics, ordinary statistical workers, and even literary figures. Early reliance on Soviet-inspired methods of enumeration became increasingly untenable in China by the middle of the 1950s. A series of unprecedented and unexpected exchanges with Indian statisticians followed, as the Chinese sought to learn about the then exciting new technology of random sampling. These developments were, in turn, overtaken by the tumult of the Great Leap Forward (1958-1961), when both probabilistic and exhaustive methods were rejected and statistics was refashioned into an essentially ethnographic enterprise. The author argues that this history, usually narrowly described as a universal, if European history, cannot be understood without acknowledging Soviet and Indian influences which not only revises existing models of Cold War science but also globalizes the wider developments in the history of statistics and data. For historians of China and social science, and political scientists, sociologists, and anthropologists studying modern China"--